The Role of Teachers in Shaping Students’ Discipline and Responsibility Character at State Elementary School Puncu 2, Kediri Regency - Khoirul Anam; Agus Tinus; Kuncahyono Kuncahyono (Journal of General Education and Humanities, 2026)
This study examines how teachers contribute to the development of discipline and responsibility among elementary students, focusing on State Elementary School Puncu 2 in Kediri Regency. The research aims to examine the specific roles teachers play in fostering these character traits and to identify supporting and inhibiting factors that Influence their implementation. A qualitative case study design was applied, involving teachers and upper-grade students as participants. Data were gathered through classroom observations, semi-structured in-depth interviews, and document analysis, and examined using an interactive analytical framework comprising data reduction, data presentation, and conclusion drawing. Credibility was strengthened through source and technique triangulation. The findings reveal that teachers function as moral exemplars, facilitators, classroom organizers, and evaluators in cultivating students’ discipline and responsibility. Character formation is implemented through structured habituation, consistent rule enforcement, reflective habit journals, classroom duty systems, daily task checklists, and positive reinforcement strategies. The effectiveness of these efforts is supported by strong teacher commitment, principal leadership, collaborative engagement with parents, and a conducive school culture. Conversely, variations in family background, inconsistent reinforcement at home, and limited student self-awareness present notable challenges. Overall, the study concludes that sustained teacher consistency, school-family partnership, and an enabling educational environment are decisive factors in successfully embedding discipline and responsibility at the elementary level.